Finite element analysis of the Longitudinal Half Fixed Beam method for mode III characterization. (15th January 2020) - Bonhomme, Jorge; Mollón, Victoria; Viña, Jaime; Argüelles, Antonio
Abstract: In this work, the Longitudinal Half Fixed Beam test (LHFB) for mode III characterization is analysed by means of Finite Element Analysis (FEA) and optical microscopy. The obtained results were compared with experimental data and analytical formulations obtained in previous works. The objective of this study is to determine the energy distribution across the crack front and to understand the micromechanics that give rise to the delamination failure in unidirectional carbon/epoxy composites. It was found that for samples with long initial crack lengths (i.e. a0  = 30 mm), pure mode III takes place in the central part of the delamination front. Nevertheless, these samples present a significant contribution of mode II at the edges of the specimen. As a0 decreases, pure mode III increases in extension across the delamination front and mode II decreases at the sample edges. When the initial crack length ( a0 ) is quite small, the sample presents pure mode III practically on the entire length of the crack front. Nevertheless, when the initial crack is very small, the applied force exercises a local influence on the tip of the crack at the edge of the sample and mode III distribution loses its uniformity across the crack front. The concordance between the analytical results and the numerical results obtained by the Finite Element Method (FEM) was variable depending on the length of the crack and if the comparison was made with GIII or GT as reference. Intralaminar cracks at approximately 45° with respect to the midplane were observed in planes perpendicular to the direction of delamination propagation (planes perpendicular to the fibre direction). Other authors also found this type of intralaminar cracks in other mode III test configurations.